2020
DOI: 10.1101/2020.08.19.20177477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine learning based clinical decision support system for early COVID-19 mortality prediction

Abstract: The coronavirus disease 2019 (COVID-19) is an acute respiratory disease that has been classified as a pandemic by World Health Organization (WHO). The sudden spike in the number of infections and high mortality rates have put immense pressure on the public medical systems. Hence, it is crucial to identify the key factors of mortality that yield high accuracy and consistency to optimize patient treatment strategy. This study uses machine learning methods to identify a powerful combination of five features that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Studies have shown that use of steroids like Dexamethasone lowered COVID-19 fatalities significantly when administered to patients who require supplemental oxygen [28–31]. We observed a relation between the usage of these drugs and the survival of patients with extreme lymphocytes and neutrophils counts, which are associated with mortality(Figure 8) [14, 15, 24, 32, 33].…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Studies have shown that use of steroids like Dexamethasone lowered COVID-19 fatalities significantly when administered to patients who require supplemental oxygen [28–31]. We observed a relation between the usage of these drugs and the survival of patients with extreme lymphocytes and neutrophils counts, which are associated with mortality(Figure 8) [14, 15, 24, 32, 33].…”
Section: Discussionmentioning
confidence: 64%
“…Karthikeyan et.al. [15] built a neural network that predicted mortality in Wuhan cohort with an accuracy of 96.5% ± 0.6% using only five parameters, age, lymphocyte (%), neutrophil (%), LDH and CRP. The same model when tested on the Indian cohort (current dataset) predicted mortality with an accuracy of only 58%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations